State of play: Climate-smart Agriculture in Africa - Trautman, Sabrina; Gosling, Amanda; Mutamba, Manyewu (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This summary presentation gives context on the current state of CSA in Africa, providing relevant cases and highlighting key action areas for transitioning toward climate-resilient, inclusive and productive agricultural systems.